Effect of Chitosan on the Growth Performance of Red Tilapia (Oreochromis mossambicus × Oreochromis niloticus) and Lettuce (Lactuca sativa L.) in Aquaponic System - Méndez-Martínez, Yuniel; Zurita-Albán, Alba D.; Zambrano-Ostaiza, Agustín N.; Pérez, Juan Jose Reyes; Antunes, Luiz Fernando de Sousa (Fronteira: Journal of Social, Technological and Environmental Science, 2025)
Aquaponics is a sustainable alternative that integrates the symbiotic cultivation of aquatic organisms and plants, whose performance can be enhanced through natural biostimulants such as chitosan. This study evaluated the bioproductive response of hybrid tilapia (Oreochromis mossambicus × O. niloticus) and three varieties of lettuce (Lactuca sativa L.) in a nutrient film technique (NFT)-type aquaponic system under different concentrations of chitosan. In lettuce cultivation, a full factorial 3×3 design (chitosan dose × lettuce variety) was implemented, with three treatments (A1: 0 ppm, A2: 500 ppm, A3: 1000 ppm) and three lettuce varieties (B1: Grandes Lagos, B2: Regina 500, B3: Red Rock), with three replicates per combination. For the fish, a unifactorial design was applied using the same chitosan concentrations. Growth performance variables in tilapia (final weight, length, specific growth rate, feed conversion ratio, and protein efficiency ratio) and agronomic parameters in lettuce (fresh weight, number of leaves, and height) were evaluated. Results indicated that the 1000 ppm chitosan treatment (A3) significantly improved (P < 0.05) fish performance, reaching an SGR of 2.56, FCR of 1.05, and PER of 2.12. In lettuce, the A2B2 and A3B1 interactions yielded the best agronomic performance (P < 0.05). Principal component analysis and Pearson correlation revealed positive associations between chitosan application and the productivity of both species. In conclusion, chitosan enhanced the integrated growth of tilapia and lettuce in the aquaponic system, representing a functional alternative for system optimization. .